Analisis Falsafah Politik John Locke Dan Aplikasinya Terhadap Integrasi Irian Barat - Saleh Djatah, Stenly Djalaludin (2011)
This thesis attempts to unravel the compelling ideas found in John Locke’s Two Treatises of Government. It is assumed that those ideas can be applied to interpreting relevant documents that pertain to the 1969 integration of Irian Jaya (West Irian) into the Republic of Indonesia. In order to achieve the purposes of this thesis, the method of topical interpretation will be used to read Locke’s work and those relevant documents. The Two Treatises of Government contains a political philosophy predicated upon three fundamental and mutually related concepts of the State of Nature, Consent, and Political Power. Political power originates from consent and consent exists on account of the state of nature.